Pengaruh Literasi Keuangan terhadap Keputusan Investasi The Jak Mania pada Rencana Initial Public Offering PT. Persija Jakarta - Thomas Mahendra; Aries Heru Prasetyo (Research Center and Case Clearing House PPM School of Management, 2021)
The evolution of football in Indonesia have another way to gain fund apart from the sales, football club in Indonesia have its own plan to be listed on The Indonesia Stock Exchange. Persija Jakarta have a plan to do an Intial Public Offering in the near future. The Jak Mania is the supporter of the Persija Jakarta Football Club. The Jak Mania must have a good investment decision if they want to invest in the Persija shares, because the investment will produce a good return. The OECD said that the financial literation is the combination of awarness, knowledge, skill, attitude, and behaviour that needed to get financial decision and achieve a good individual financial being. This research is aim to know is the financial literation with indicator financial knowledge, financial attitude, andfinancial behaviour have a positive and significant influences to the investment decision on the Initial Public Offering Persija Jaya Jakarta with The Jak Mania as the sample. This Research used questionnaire as the method with purposive sampling tehnic with 232 respondend. The result of this research is knowing that financial knowledge, financial attitude, and financial behaviour have a positif and significant influences to invesment decision of The Jak Mania on Initial Public Offering of PT Persija Jaya Jakarta